Desempenho zootécnico de bezerras da raça holandesa alimentadas com diferentes volumes de sucedâneo do leite - Pires, Suzana da Cruz (2014)
The heifers breeding for replacement of dairy herds have great importance for the national livestock. This breeding phase is critical and challenging due to numerous factors, but mainly when it comes to feeding management. The aim of this work was to evaluate the effect of three different volumes of milk replacer, provided for Holstein heifers up to 60 days, on the zootechnical performance and the relation cost-benefit of production. The work was carried out at the heifers Rearing Unit of Cooperativa Agroindustrial Lar in São Miguel do Iguaçu - PR. 45 heifers were used, randomly allocated into three treatments. With the use of an automatic feeder, the treatments were based on offering three different amounts of milk replacer: 4L Treatment (four liters); 6L (six liters) and AL (ad libitum). All animals received concentrate ad libitum. The morphometric measurements (height, body length, chest girth) and weight were measured weekly. The used experimental outline was completely randomized. It was performed the variance analysis and for comparison of means it was used Tukey at 5% significance. Data were analyzed by statistical program Sisvar. 4L and 6L heifers had higher concentrate intake than AL heifers. The feeding cost of 4L and 6L heifers was 66.42 and 90% respectively lower compared to AL heifers. AL heifers showed higher weight averages and morphometric measurements than other treatments in most of weeks. Regardless of the milk replacer volume supplied, 4L heifers showed higher concentrate intake and lower production cost. The zootechnical performance was similar for all treatments at weaning